Cardiac Derived CD51-Positive Mesenchymal Stem Cells Enhance the Cardiac Repair Through SCF-Mediated Angiogenesis in Mice With Myocardial Infarction - Xie, Dong Mei; Chen, Yang; Liao, Yan; Lin, Wanwen; Dai, Gang; Lu, Di Han; Zhu, Shuanghua; Yang, Ke; Wu, Bingyuan; Chen, Zhihong; Peng, Chaoquan; Jiang, Mei Hua (Frontiers in Cell and Developmental Biology, 2021)
Objective: Many tissues contained resident mesenchymal stromal/stem cells (MSCs) that facilitated tissue hemostasis and repair. However, there is no typical marker to identify the resident cardiac MSCs. We aimed to determine if CD51 could be an optimal marker of cardiac MSCs and assess their therapeutic potential for mice with acute myocardial infarction (AMI). Methods: Cardiac-derived CD51+CD31–CD45–Ter119– cells (named CD51+cMSCs) were isolated from C57BL/6 mice(7-day-old) by flow cytometry. The CD51+cMSCs were characterized by proliferation capacity, multi-differentiation potential, and expression of typical MSC-related markers. Adult C57BL/6 mice (12-week-old) were utilized for an AMI model via permanently ligating the left anterior descending coronary artery. The therapeutic efficacy of CD51+cMSCs was estimated by echocardiography and pathological staining. To determine the underlying mechanism, lentiviruses were utilized to knock down gene (stem cell factor [SCF]) expression of CD51+cMSCs. Results: In this study, CD51 was expressed in the entire layers of the cardiac wall in mice, including endocardium, epicardium, and myocardium, and its expression was decreased with age. Importantly, the CD51+cMSCs possessed potent self-renewal potential and multi-lineage differentiation capacity in vitro and also expressed typical MSC-related surface proteins. Furthermore, CD51+cMSC transplantation significantly improved cardiac function and attenuated cardiac fibrosis through pro-angiogenesis activity after myocardial infarction in mice. Moreover, SCF secreted by CD51+cMSCs played an important role in angiogenesis both in vivo and in vitro. Conclusions: Collectively, CD51 is a novel marker of cardiac resident MSCs, and CD51+cMSC therapy enhances cardiac repair at least partly through SCF-mediated angiogenesis.